Globalisation, reflexive modernisation, and development: the case of India - Pick, David; Dayaram, Kandy (2006)
Purpose: the purpose of this paper is to use the theoretical insights provided by reflexive modernisation in examining the effects of globalisation on the development policies and trajectories of India.Approach: after a presentation of the main ideas and concepts of reflexive modernisation and globalisation, the principal characteristics of the reflexive modernisation of India are identified and discussed.Findings: this paper demonstrates that the development path taken by India is characterised by ambiguity, contradiction, and paradox. There is much doubt, uncertainty, and debate in academic, political, and social forums about whether India is on the right development path as the nation attempts to graft western-style capitalist structures and technologies onto traditional ways of life. Indeed, in its drive towards economic development and enhanced social well-being India is at the same time compromising that development and well-being through the production of risks.Limitations: there are two main limitations of this paper. The first relates to reflexive modernisation. It is a much discussed and controversial theory that requires further enhancement, particularly with regard to developing nations. The second relates specifically to India in that it is difficult to make generalisations about such a diverse nation.Implications: in spite of its limitations, reflexive modernisation offers a sound theoretical foundation for alternative perspectives and policy approaches to development. As developing nations such as India engage with global economic, cultural, and political structures and institutions, they are at the same time transforming and being transformed by the influences that these structures and institutions exert.